KEPEMIMPINAN KEPALA SEKOLAH DALAM PENINGKATAN KINERJA GURU DAN MUTU PENDIDIKAN DI MADRASAH IBTIDAIYAH NEGERI 26 HULU SUNGAI UTARA - Majidi, Majidi; Muhammad Yuliansyah, (Journal of Innovation Research and Knowledge, 2025)
This study aims to explore the principal's leadership in improving teacher performance and the quality of education at State Elementary School 26 Hulu Sungai Utara. The focus includes the principal's leadership style, strategies implemented to improve the quality of education, and obstacles faced in the process. The results of the study indicate that the principal's leadership at State Elementary School 26 Hulu Sungai Utara is carried out through clear planning, division of tasks according to teacher potential and moving them to achieve goals. The leadership styles applied include informing, situational, selling, and participatory-democratic styles to direct, guide and train teachers. The strategies include being a role model, implementing discipline and providing facilities and infrastructure to motivate teachers. The main obstacle is the lack of textbooks or assignment sheets, which hinders the improvement of students' insights, especially those from low-income families.